2016
DOI: 10.1128/aac.01539-15
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Bioactivity Evaluation, and Toxicity Assessment of Novel Salicylanilide Ester Derivatives as Cercaricides against Schistosoma japonicum and Molluscicides against Oncomelania hupensis

Abstract: A series of novel salicylanilide ester derivatives were synthesized, characterized, and evaluated for cercaricidal potential against Schistosoma japonicum and molluscicidal potential against Oncomelania hupensis. Four derivatives exhibited remarkable cercaricidal activity superior to that of niclosamide. Among them, the most active compound, 4-chloro-2-((2-methoxy-4-nitrophenyl)carbamoyl)phenyl 4-methoxybenzoate (compound 4c), showed a marked minimum effective cercaricidal concentration as low as 0.43 M and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
1
11
0
3
Order By: Relevance
“…Niclosamide was used as positive control, and dechlorinated water mixed with DMSO (no compounds) was used as a negative control. Snails were considered dead according to one or more of the following criteria: discoloration, contraction of the hemolymph [ 21 ], absence of muscle contraction and heart activity [ 22 ], hemorrhage and deterioration of the body tissues [ 19 ]. The 50%/90% lethal concentration (LC 50 /LC 90 ) values, as well as their 95% confidence limits, were determined through probit analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Niclosamide was used as positive control, and dechlorinated water mixed with DMSO (no compounds) was used as a negative control. Snails were considered dead according to one or more of the following criteria: discoloration, contraction of the hemolymph [ 21 ], absence of muscle contraction and heart activity [ 22 ], hemorrhage and deterioration of the body tissues [ 19 ]. The 50%/90% lethal concentration (LC 50 /LC 90 ) values, as well as their 95% confidence limits, were determined through probit analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies demonstrated that a salicylanilide ester derivative exhibited similar activity against Oncomelania hupensis and negligible toxicity to human kidney cells and Danio rerio compared with that of niclosamide [ 19 ]. Based on these findings, salicylanilidate was optimized as a novel compound from niclosamide by 4-methoxyphenyl ester substituent at the hydroxyl group and then evaluated for cercaricidal potential against S. mansoni and molluscicidal potential against crucial intermediate hosts of S. mansoni in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…e broad toxicity of niclosamide to many nontarget organisms such as fish and amphibians is the major concern against its use in mass application [5]. us, there are new attempts to develop novel molluscicides by optimizing the activity of known substances or tapping diverse compounds from natural sources [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…ere is a growing interest in phytochemicals with potent molluscicidal activity a er the successful use of Phytolacca dodecandra in the snail population control of schistosome vectors in Egypt [7,8,11]. Synthesis of new compounds and structure-activity relationship with known molluscicides are also gaining popularity [9,10,12,13]. Both research strategies will require an assay which uses a small amount of test substance while maintaining accuracy and reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…Pela ausência de vacina, as ações que se têm realizado para combater a parasitose são inquéritos malacológicos, o diagnóstico e o tratamento dos esquistossomóticos com o fármaco praziquantel(PEREIRA et al, 2017). Estas atividades têm diminuído o índice de formas clínicas graves, porém não têm reduzido a prevalência e nem impedido a transmissão da endemia, de forma que o doente pode adquiri-la novamente(CANTANHEDE et al, 2010).Em função destas circunstâncias, muitos pesquisadores sugerem como estratégia promissora para o controle da helmintíase em médio e longo prazo o controle dos moluscos hospedeiros conjugado com a quimioterapia, as obras sanitárias e as práticas de educação em saúdeCALDEIRA, 2016;WANG et al, 2016;.O controle dos caramujos transmissores pode ser realizado, dentre outros métodos, por meio da aplicação de moluscicidas nos seus criadouros naturais. O moluscicida sintético niclosamida, comercialmente conhecido como Bayluscide®, possui alta eficiência contra todos os estágios de desenvolvimento dos caramujos Biomphalaria e formas larvárias de Schistosoma(BRASIL, 2008;MATA et al, 2011;MARTINS et al, 2017).…”
unclassified